Lithofacies and mineralogy of the estrada nova formation in the state of são paulo, brazil, aiming application in the ceramic coating industry - Christofoletti, Sérgio Ricardo; Roveri, Carolina Del; Zanardo, Antenor [UNESP] (My University, 2020)
The objective of this work is to characterize the sedimentary lithofacies and mineral composition of the Estrada Nova Formation, in the south-central region of the São Paulo State. The faciological description associated with the mineralogical characterization has proved to be an important tool in the preliminary evaluation of the rocks of the Estrada Nova Formation as raw material for the ceramic industry. Five lithofacies were identified: Laminated Siltstone Shales, Massive Siltstone, Laminated Siltstone, Intercalated Siltstone and Rhythm Sandy. The lithofacies of the Serra Alta Member according to their characteristics indicated deposition in a deep platformal environment offshore in the process of low energy sedimentation, sometimes combined with traction processes, which led to the formation of fine-grained sandstone beds with planar parallel laminations. In the Teresina Member, it was observed that the lithofacies presents red color, coarse lithology and an increase of sandstone layers with carbonate cementation toward the top forming rhythmic bedding. The presence of sandstone beds in the intermediate portions and top of the Teresina Member can be related with variations of the tides and reworking by waves in lower shoreface environment. The red color indicates the transition from a reducing to an oxidant environment. The high presence of carbonates indicates a shallow marine environment characterized by and reddish, an oxidizing environment in the formation of these lithofacies. The X-ray analyses showed the low frequency of the albite feldspar and the illite clay minerals and the high presence of calcite, especially in the Teresina Member. The low frequency of the illite, albite and elevated of the calcite mineral, especially in the lithofacies of the Teresina Member, limits its use as a single raw material in the production of ceramic coatings. In the Serra Alta Member, the general finer sediments and more frequent presence of the illite enables its use for ceramic coating and structural industry. Subsequent technological characterization studies will define the more suitable uses for these rocks as ceramic raw materials.
Litofácies e mineralogia da formação estrada nova no estado de são paulo – brasil visando aplicação na indústria cerâmica de revestimento
Keywords: Estrada Nova Formation; Lithofacies; Mineralogy